1993
DOI: 10.1111/j.1365-2958.1993.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis PrsA is required in vivo as an extracytoplasmic chaperone for secretion of active enzymes synthesized either with or without pro‐sequences

Abstract: In prsA (protein secretion) mutants of Bacillus subtilis, decreased levels of exoproteins, including alpha-amylase and subtilisins, are found extracellularly. The effect of prsA on subtilisin secretion is elaborated here. Extracytoplasmic folding and secretion of active subtilisin is assisted by the N-terminal pro-sequence of its precursor. In this paper we present evidence that the product of the prsA gene is additionally required for these processes in vivo. We examined inducible expression of different subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 47 publications
3
98
0
Order By: Relevance
“…The first amino acid residue at the N terminus of the mature PrsA is a cysteine, which is covalently linked to a diacylglycerol molecule that anchors the protein to the membrane. It has been suggested that PrsA catalyzes or assists the post-translocational folding of extracytoplasmic proteins at the cytoplasmic membrane-cell wall interface (19,20). The secretion rate of AmyQ ␣-amylase, a model protein used in many of our studies, is linearly dependent on the cellular level of PrsA (6).…”
mentioning
confidence: 74%
“…The first amino acid residue at the N terminus of the mature PrsA is a cysteine, which is covalently linked to a diacylglycerol molecule that anchors the protein to the membrane. It has been suggested that PrsA catalyzes or assists the post-translocational folding of extracytoplasmic proteins at the cytoplasmic membrane-cell wall interface (19,20). The secretion rate of AmyQ ␣-amylase, a model protein used in many of our studies, is linearly dependent on the cellular level of PrsA (6).…”
mentioning
confidence: 74%
“…Consequently, prsA mutations result in significantly reduced amounts of cell-associated and secreted mature AmyQ, but they do not result in the accumulation of pre-AmyQ in the cell (32,33). As a first approach to identify the stage in the secretion pathway in which TepA is involved, we investigated whether TepA is active before or after PrsA.…”
Section: Resultsmentioning
confidence: 99%
“…An unexplained observation was, however, that B. subtilis cells lacking SPase II accumulated significantly increased levels of pre-AmyQ (15). As the latter effect was never observed in prsA mutant strains (17,18), it was concluded that the increased pre-AmyQ accumulation in lsp mutant strains was because of the malfunction of one or more lipoproteins other than PrsA. This formed the incentive to search for lipoproteins of B. subtilis with an as yet unknown role in protein secretion.…”
mentioning
confidence: 99%